“I would like to tatoo the illness on my arm”. The Integrated Personalized Nursing Diagnosis (IPND). - Artioli, Giovanna; Foà, Chiara; Taffurelli, Chiara; Cosentino, Chiara (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: The nursing diagnosis can based on two different approaches: the standard diagnosis, searching for regularities that can fall within pre-existing categories identified by the nurse, as the expert of the disease; the narrative diagnosis, based on personal meaning attributed to the illness, of which only the patient is the expert. The aim of this work is to underline the usefulness of integration between standard diagnosis and narrative diagnosis, through the Integrated Personalized Nursing Diagnosis (IPND). Methods: A 31 years old man, suffering from leukaemia, is welcomed at an Italian Oncological Day Hospital, by a nurse trained in the IPND approach. She used the Gordon functional models on objective data, and collected a narration about patient’s experience, which has been analyzed with a Grounded Theory methodology. Results: The narrative revealed critical issues and the priorities that patient assigns, which would not have been obtained from a standard diagnosis. From the standard diagnosis, however, emerge several aspects that the patient has neglected to narrate and that does not directly address in his story. The diagnostic integration allowed the nurse to define a conceptual map of problems and resources in a personalized manner. Conclusion: The IPND not only gives importance to the priorities of the patient, but also underlines the dynamic path, in which not only the static analysis of needs becomes significant, but also the changes that occur in attributing new meanings to the life experience, as well as the evolution of the person him/herself in this process.